Comparison of neoadjuvant immunotherapy plus chemotherapy versus chemotherapy alone for patients with locally advanced esophageal squamous cell carcinoma: A propensity score matching - Jing, Shao-Wu; Zhai, Chang; Zhang, Wei; He, Ming; Liu, Qing-Yi; Yao, Ji-Fang; Wang, Rui; Tian, Zi-Qiang; Wang, Jun; Liu, Jun-Feng (Frontiers in Immunology, 2022)
Objectives Clinical studies on immune checkpoint inhibitors (ICIs) combined with neoadjuvant chemotherapy (nCT) have been carried out for the resectable esophageal squamous cell carcinoma (ESCC). So far, few studies have compared the survival outcomes of nCT plus ICIs and nCT alone. This study aimed to compare the efficacy and safety of neoadjuvant ICIs combined with nCT versus nCT followed by esophagectomy for patients with resectable locally advanced ESCC. Methods A retrospective analysis of ESCC patients underwent nCT or nCT combined with ICIs followed by esophagectomy (from March 2013 to April 2021) was performed. A 1:1 propensity score matching (PSM) with a caliper 0.01 was conducted to balance potential bias. Results A total of 47 comparable pairs of ESCC patients receiving nCT and nCT combined with ICIs were selected for the final analysis. The tumor regression grade (TRG) 0 and pathologic complete response (pCR) rates in the nCT+ICIs group were significantly higher than those of the nCT group (21.7% vs. 4.5%, P=0.016; and 17.0% vs. 2.1%, P=0.035, respectively). The rate of nerve invasion was 4.3% in the nCT+ICIs group, significantly lower than 23.4% of the nCT group (P=0.007). The incidences of adverse events in the nCT+ICIs group were similar compared with the nCT group and there was no grade 5 toxicity in either group. The 1-, 2-year disease-free survival rates (DFS) were 95.7%, 80.7% and 76.1%, 63.8% in the two groups (P=0.001, and P=0.046, respectively). The 1-year OS was improved in the nCT+ICIs group, which was close to a statistical difference (95.7% vs. 84.8%, P=0.074). Local recurrence rate in the nCT+ICIs group was 6.4%, significantly lower than 21.3% of the nCT group (P=0.036), while there was no significant difference in the distant metastasis. Conclusions Compared with nCT alone, neoadjuvant immunotherapy plus nCT for patients with locally advanced ESCC has an advantage in pathological response, and could improve DFS with a good safety and feasibility, while long term survival validation is still needed further.